Model corporate social responsibility dalam penanganan komunikasi krisis selama pandemi covid-19 di Indonesia - Budi Sulistiyo Nugroho; Abdul Samad Arief; Firdaus Yuni Dharta; Kadek Suryani; Setyo Utomo (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
Problems or challenges that arise during the implementation of the Corporate Social Responsibility program that have been determined require company management assistance to resolve and place the company in a positive position. A list of noteworthy Corporate Social Responsibility issues includes issues that are frequently discussed, and the media can be used to help explain Corporate Social Responsibility programs to all stakeholders. This study aims to determine the Corporate Social Responsibility model in handling critical communication during the Covid-19 pandemic in Indonesia. The method used in this study is a literature review. The unit of analysis in this study is a journal article that has been obtained by researchers through Google Scholar during the 2022 period. The conclusion of this study is that the Corporate Social Responsibility model in handling critical communication during the Covid-19 pandemic in Indonesia uses a partnering model with other parties.